English as a Medium of Instruction in English for Islamic Studies: Students’ Perceptions and Outcomes at Islamic Higher Education - Fithriyah, Fithriyah; Maskur, Maskur (Intelektualita: Journal of Education Sciences and Teacher Training, 2025)
This study investigates the students’ perceptions of using English as a Medium of Instruction (EMI) in English for Islamic studies courses. Using a mixed-methods design, the research involved 50 students from the English language education department as survey participants, and 10 students were randomly selected for follow-up interviews. The findings reveal that EMI contributes positively to students’ comprehension of the subject and significantly enhance their English language proficiency. Students also reported that their confidence and motivation in taking the course improved. These insights can inform future policy and pedagogical strategies, such as implementing translanguaging practices, improving language support, and incorporating Islamic values into EMI.